Characterization and optimization of images acquired by a compact soft X-ray microscope based on a double stream gas-puff target source. (4th April 2016) - Torrisi, A.; Wachulak, P.; Nawaz, M. Fahad; Bartnik, A.; Węgrzyński, L.; Jancarek, A.; Fiedorowicz, H.
Abstract: Using a table-top size soft X-ray (SXR) microscope, based on a laser plasma source with a double stream gas-puff target and a Fresnel zone plate objective, series of images of test samples were acquired. Characterization and optimization of the acquisition parameters were studied and evaluated in terms of signal to noise ratio (SNR). Conclusions for the optimization of SXR imaging were reached. Similar SNR measurements might be performed to characterize other SXR imaging systems as well. Software enabling live calculation of the SNR during the image acquisition might be introduced in future in the compact imaging systems for optimal image acquisition or for benchmarking purposes.